Multiple functions of S100A10, an important cancer promoter. Issue 11 (14th October 2019) - Saiki, Yuriko; Horii, Akira
Abstract : The S100 group of calcium binding proteins is composed of 21 members that exhibit tissue/cell specific expressions. These S100 proteins bind a diverse range of targets and regulate multiple cellular processes, including proliferation, migration and differentiation. S100A10, also known as p11, binds mainly to annexin A2 and mediates the conversion of plasminogen to an active protease, plasmin. Higher S100A10 expression has been reported to link to worse outcome and/or chemoresistance in a number of cancer types in lung, breast, ovary, pancreas, gall bladder and colorectum and leukemia although some discrepancy was reported. In this review, we focused on the roles of the S100A10 in cancer. We summarized its biological functions, role in cancer progression, prognostic value and targeting of S100A10 for cancer therapy.